Entrepreneurship in social media - Tiviakova, Anastasiia (Creativity in Business Practice. Part 2, 2019)
The chapter relates to the importance of social media for a contemporary entrepreneur, as well as presents the advantages and disadvantages of using social media in running a business. The study is based on scientific publications in which specialists from countries such as Poland, Russia and the United States of America present their vision of entrepreneurship in social media. The aim was to demonstrate the practical utility of social media in running a company, and familiarize with concepts such as entrepreneurship and social media.